COMP-08. COMPREHENSIVE RNA ANALYSIS OF CEREBROSPINAL FLUID FROM LEPTOMENINGEAL METASTASES. (11th November 2019) - Polyak, Dina; Li, Yingmei; Liu, Boxiang; Connolly, Ian; Khoeur, Lina; Wasunga Kakusa, Bina; Johnson, Eli; Andersen, Stephanie; Pan, Wenying; Nagpal, Seema; Montgomery, Stephen B; Hayden Gephart, Melanie
Abstract: Leptomeningeal metastases (LM), a diffuse form of brain metastases is rare and fatal progression of non-small cell lung cancer (NSCLC). In LM, metastatic cancer cells spread and resign on the brain meninges, the cerebrospinal fluid (CSF), cranial and spinal nerves. Rapid disease progression and scarce tissue availability hinder the progress of scientific study of LM and its treatment. To overcome the critical lack of tissue and to determine the genetic profile of NSCLC LM, we have developed methods to extract tumor-associated cell-free RNA from CSF, and isolated and sequenced circulating single cells from CSF. Herein, we used high throughput qPCR to target lung and brain-associated genes and identified NSCLC LM metastases-related RNA. Brain-specific gene signature (GFAP, NRGN, SNCB, ZBTB18) was detected in all CSF sample (control and metastases), whereas lung-specific genes (MUC1, SFTPB, SFTPD, SLC34A2) were detected in CSF of brain metastases patients. Normal, healthy CSF lacks cellular component, but CSF of patients with LM metastases inhabited with very low amount of circulating tumor cells. Single cells from CSF of 4 patients with NSCLC LM metastases were captured with microfluidic chip. Cells (n = 197) were clustered by significantly differential expressed genes demonstrating two distinct populations of white blood and tumor cells. These data identified specific cfRNA and single cell transcriptome profiles compared to normal cells or patients without NSCLC LM metastases, and highlighted metastases-associated carcinoembryonic antigen-related cell adhesion molecule 6 (CEACAM6) as highly expressed in patients with NSCLC LM metastases. CEACAM6 mRNA was detected in CSF of 86% of patients with NSCLC LM but not in the CSF of control patients. In vitro inhibition of CEACAM6 protein lead to decreased invasion in NSCLC cells which was rescued by overexpression of the protein. We have developed sensitive and robust techniques to leverage human CSF to study NSCLC LM.